The Airways' Mechanical Stress in Lung Disease: Implications for COPD Pathophysiology and Treatment Evaluation. (5th September 2019) - Santus, Pierachille; Pecchiari, Matteo; Tursi, Francesco; Valenti, Vincenzo; Saad, Marina; Radovanovic, Dejan
Abstract : The airway epithelium stretches and relaxes during the normal respiratory cycle, and hyperventilation exaggerates this effect, resulting in changes in lung physiology. In fact, stretching of the airways influences lung function and the secretion of airway mediators, which in turn may cause a potentially injurious inflammatory response. This aim of the present narrative review was to illustrate the current evidence on the importance of mechanical stress in the pathophysiology of lung diseases with a particular focus on chronic obstructive pulmonary disease (COPD) and to discuss how this may influence pharmacological treatment strategies. Overall, treatment selection should be tailored to counterpart the effects of mechanical stress, which influences inflammation both in asthma and COPD. The most suitable treatment approach between a long-acting β 2-agonists/long-acting antimuscarinic-agonist (LABA/LAMA) alone or with the addition of inhaled corticosteroids should be determined based on the underlying mechanism of inflammation. Noteworthy, the anti-inflammatory effects of the glycopyrronium/indacaterol combination on hyperinflation and mucociliary clearance may decrease the rate of COPD exacerbations, and it may synergistically improve bronchodilation with a double action on both the cyclic adenosine monophosphate (cAMP) and the acetylcholine pathways.